A Validated RP-HPLC Method for Simultaneous Estimation of Nebivolol and Hydrochlorothiazide in Tablets - Meyyanathan, S. N. (Medknow Publications, 2008)
A simple, selective, rapid, precise and economical reverse phase high pressure liquid chromatographic method has been developed for the simultaneous estimation of nebivolol and hydrochlorthiazide from pharmaceutical formulation. Phenomenex Gemini C(18) (25 cm×4.6 mm i.d., 5 μ) column with a mobile phase consisting of acetonitrile: 50mM ammonium acetate (adjusted to pH 3.5 using orthophosphoric acid) (70:30 v/v) at a flow rate of 1.0 ml/min was used. Detection was carried out at 254 nm. Probenecid was used as an internal standard. The retention times of probenecid, nebivolol and hydrochlorthiazide were 13.05, 3.32 and 4.25 min, respectively. The developed method was validated in terms of accuracy, precision, linearity, limit of detection, limit of quantitation and solution stability. The proposed method can be used for the estimation of these drugs in combined dosage forms.